2020
DOI: 10.14716/ijtech.v11i2.3279
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of a Hydrophobic Silica Nanoparticle Composite Membrane for Oil-Water Emulsion Separation

Abstract: The superhydrophobic composite membrane was successfully manufactured by a sol-gel method by drying the surrounding pressure. Tetraethylorthosilicate (TEOS) was used as a hydrophobic agent, while waterglass was used as a source of silica. The effect of the water to waterglass ratio (noted at 16:1 and 19:1) was evaluated to study the hydrophobic properties of the silica film coated composite membrane surface. By measuring the water contact angle on the film surface, the highest contact angle was found to occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…However, the use of 10 mL water volume led to a contact angle of 45.08°. These results are in accordance with previous researchers concerning the effect of the ratio of water to glass with TEOS as a modifying agent 41) . The resulting contact angle increased and also decreased to 143.86±0.43° and 141.70±0.63°, respectively.…”
Section: Effect Of Water Volume On Contact Anglesupporting
confidence: 93%
See 1 more Smart Citation
“…However, the use of 10 mL water volume led to a contact angle of 45.08°. These results are in accordance with previous researchers concerning the effect of the ratio of water to glass with TEOS as a modifying agent 41) . The resulting contact angle increased and also decreased to 143.86±0.43° and 141.70±0.63°, respectively.…”
Section: Effect Of Water Volume On Contact Anglesupporting
confidence: 93%
“…This causes the hydrophobic structure of silica to be weak. When the silica pores containing ethanol are dried, the ethanol evaporates along with Si-NH2, thereby reducing surface hydrophobicity 41) .…”
Section: Effect Of Water Volume On Contact Anglementioning
confidence: 99%
“…In recent times, nanotechnology has been integrated in many parts of our everyday lives. The fabrication of organic and inorganic nano-and microcrystals is one area of growing interest from the perspectives of both fundamental science and applications (Poerwadi et al, 2020;Strokova et al, 2020). However, organic microcrystals have received little attention so far because of difficulties with their characterization and the thermal instability of most of the organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinyl chloride (PVC) is a versatile thermoplastic polymer that shows appropriate chemical and biological resistances for water applications (Giwa et al, 2019). Inorganic nanoparticles are frequently incorporated into polymeric membrane matrixes to increase the membranes' performance, including functionality and thermal, chemical, and mechanical stability (Poerwadi et al, 2020). Developments in ion exchange membranes with the introduction of inorganic nanoparticles using aluminum oxide (Hosseini et al, 2012), titanium oxide (Nemati et al, 2015), and iron oxide (Hong and Chen, 2014) have been reported.…”
Section: Introductionmentioning
confidence: 99%